(3LQjeI GdMQGHI hYbhHJgG aj GdTQjYI GdESdGejI hGdbGfhf GdLfGFj (B: s (3OQGSI ebGQfI (B/ s - (3YHO GdYRjR eMeO eMeO eMSfs; (3eCehf eMeO SdGeI (B: s; (3jhSa eMeO eMehO bGSe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1983)
(3jJcde JegjO gPG GdHMK HGjLGR Yf GdeUGdM GdeYJHQg ai GdJTQjY GdGSdGei VQhQjI cGfJ Gh MGLjg Gh JMSjfjg hcPdc JYQja GdLQjeg hCQcGfgG heQGMd JchjfgG hJYQja GdYbhHg GdJi TQYgG Gddg dgPg GdeUGdM ShGA cGfJ gPg GdYbhHg MOG Ce bUGUG Ge JYRjRG eY HjGf GhLg GdaQb Hjf cd ef gPg GdYbhHGJ Ke jfbSe GdHMK Gdi bSejf QFjSjjf jYGdL GdHGH GdGhd ef GdbSe GdGhd LQjeg GdMQGHI ai GdTQjYg hGdbGfhf ef MjK Chd GQcGf LQjeg GdMQGHg hgh y aYd GdMQGHg y ai GdTQjYg hGdbGfhf hKGfi GQcGf gPg GdLQjeg hgh yGdeMGQH Ke KGdK GQcGfgG hgh y GdeMGQH Ydjgy hCNjQG QGHY GQcGf LQjeg GdMQGHg hgh GdbUO GdLfGFi y cd Pdc ai GdTQjYg hGdbGfhf CeG GdHGH GdKGfi agh NGU HWQb GKHGJ LQjeg GdMQGHg ai GdTQjYg hGdbGfhf hbO egO dg HOQGSI GdOYhi hef dg Mb QaYgG ai GdTQjYg hGdbGfhf Ke jfGbT ehVhYi GdGbQGQ hGdTgGOg Ke Gdjejf GdeQOhOg Ydi GdeOYi hGdbQGFf CeG GdbSe GdKGfi ef GdHMK ajTeJed Ydi JegjO ai adSag YbhHg GdMQGHg Hjf GdJfhjY hGdJNjjQ hBQGA GdabgGA ai Pdc eY HjGf YbhHJi LQjeg GdMQGHg ai GdMGd GdGhdi hai GdMGdg GdKGfjg hCNjQG HjGf Mce GdeGd GdeCNhP MQGHI hjbY Pdc ai GdHGH GdGhd ef gPG GdbSe Ke jCJi GdHGH GdKGfi djfGbT OQA GdMO hSbhWg ceG jfGbT HYV GdeSGFd GdefKhQI hgi Mce ZjQ GdeHGTQ hGdeSFhdjg GdJVGefjg GdeOjfg aj LQjeg GdMQGHI heG jJQJH Ydi GdNWC aj JfajP MO GdbWY Ydi GdeMGQH hJYdjb jO hQLd GdeMGQH aj Yfbg hGNjQG hLhO GdeGd GdeCNhP MQGHg YfO ZjQ GdeMGQH Ke JCJi NGJeg GdHMK hJTJed Ydi GdJYQa Ydi GSHGH LQjeg GdMQGHI hYdGLgG hhGLH GdMGce hGaQGO GdeLJeY fMh eQJcHi GdLQjeg GdTfYGA hMce GdbhGfjf GdeNJdag ddTQjYg GdGSdGejg ceG JTed Ydi fJGFL GdHMK hefGTOI Gdi JWHjb GMcGe GdTQjYg GdGSdGejg HUag YGeg hMO GdMQGHg HUag NGUI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1983.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ(B: 637- 677.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdeUGdM GdeYJHQI HGdJTQjY GdESdGejs; (3JYQja GdMQGHIs; (3GdTQhY aj LQjeI GdMQGHIs; (3CQcGf LQjeI GdMQGHIs; (3UhQ JMbb LQjeI GdMQGHIs; (3ecGf LQjeI GdMQGHIs; (3ReGf JMbb GdMQGHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs